Lifestyle, Nutritional Status and Seroclinical Profile of Liver Cirrhotic Patients - Ahsan, Touhida; Ahsan, Monira; Kamal, Md Mustafa; Hossain, Kaji Jahangir; Haque, Mohammed Emdadul; Islam, SK Nazrul (Bangladesh Medical Journal, 2009)
Liver cirrhotic patients were investigated for their lifestyle, energy intake, BMI, biochemical and serological indices and prevalent clinical signs. The study included 50 liver cirrhotic patients who were hospitalized in Bangabandhu Sheikh Mujib Medical University, Dhaka Medical College Hospital and BIRDEM Hospital during the period of 1999-2000. Of the fifty cirrhotic patients, hepatitis B virus infection was found responsible for 52% (n=26) of liver cirrhosis, hepatitis C was for only 6% (n=3) patients and etiology for the rest 42% (n=21) patients could not be identified. It was observed that literate, low-mid income and productive male were being suffering from the liver cirrhosis. The patients had good housing status. Low energy intake (1670.6±42.9) and low BMI (19.52±3.48) were present in almost all of the patients. Mean serum haemoglobin, total proteins, and albumin were 96.2±20.5g/L, 63.1±1.01g/L, and 31.30±0.93g/L respectively. Serum bilirubin was raised in 50% patients. Serum SGPT and SGOT levels were increased from 2 to 4 folds in 50% of the patients; alkaline phosphatase was increased only in 8% cirrhotic patients. Anaemia, PEM, ascities, oedema, muscle wasting were prevalently present in vast majority of the patients. Key words: Liver cirrhosis, nutritional status, liver function determinants DOI: 10.3329/bmj.v36i2.3611 Bangladesh Medical Journal 36(2) 2007 44-47